Spatial variations in the character of off-the-books entrepreneurship: lessons from a study of contrasting districts in Moscow. (10th May 2010) - Williams, Colin C.; Round, John
Although there is growing recognition that many entrepreneurs start up trading partially or wholly off-the-books, few have evaluated whether the character of this hidden enterprise culture varies spatially. To begin to do so, this paper evaluates whether and how the nature of off-the-books entrepreneurship differs across an affluent, a mixed and a deprived district of Moscow. Drawing upon 313 face-to-face interviews, the finding is that wholly legitimate enterprises represent just the tip of the iceberg in Moscow. Beneath the surface in all the districts is a large hidden enterprise culture. However, off-the-books entrepreneurship in the affluent district is composed more of registered businesses trading partially off-the-books and conducted as a voluntarily chosen spin-off from their formal employment. In the deprived district, meanwhile, it is composed more of unregistered wholly off-the-books businesses and such entrepreneurship is largely a survival tactic and last resort. The paper concludes by discussing the theoretical and policy implications of these findings.